Spatial Analysis of Rainfall in Rio Grande Do Norte State, Brazil - Luna Lucena, Rebecca; Monteiro, Francisco; Mariz Faria, Raila; Santiago Reis, João (Revista Geográfica de América Central., 2024)
The main goal of this research was to perform a spatial analysis of precipitation in the state of Rio Grande do Norte (RN) through geostatistical techniques, comparing the historical average data with rainy and dry standard years. Three indicators called Moran's Global Index, Moran Map, and Moran's Scattering Diagram were used for geostatistical analysis. The results showed that precipitation has a more evident pattern in the Eastern Potiguar mesoregion since both in the year considered rainy and, in a year considered dry, most of this mesoregion presented a (HH) pattern, that is, the municipalities form a cluster that represents spatial autocorrelation associated with higher values of precipitation in the state. The regions of Agreste and Central Potiguar were the driest.